Pengujian Fungsionalitas Aplikasi Kasir Berbasis Web dengan Metode Blackbox - Firima Halawa; Aries Saifudin (CV. Multi Kreasi Media, 2023)
Nowadays, computers have an important role in human life. Because computers really help humansin carrying out tasks through the applications and features available according to human needs. Most of the people who have a business doing all their activities are more computerized on a regular basis for reasonsof time, less risk and faster decisions than without a computer. For this reason, the purpose of this study isresearch aims to evaluate the effectiveness of using Selenium in functional testing of web-based point of sale (POS) application using the blackbox method. Selenium is an automated testing tool used to test web applications by recording and playing back user actions on the browser. The blackbox method is used to examine the application's functions from the user's point of view without checking the implementation details of the source code or the internal structure of the application. This research uses a web-based POS application as a case study and performs functional testing using the blackbox method with and without using Selenium. The test results show that using Selenium in functional testing of web-based POS application with blackbox method can improve the effectiveness and efficiency of testing, as well as ensure that the application functions properly and meets the user's needs. This research contributes to the development of web-based POS application testing methods using automated tools such as Selenium to improve the effectiveness and efficiency of testing.